Analisis Visual Kampanye Kesehatan Bone Marrow Donor Programme X Blak Labs - Atalla, Rayyan (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2024)
Visual analysis of the social campaign design "Bone Marrow Donor Program x Blak Labs" reveals a creative approach in promoting awareness of the importance of being a bone marrow donor. This research explores the visual design strategies used in this social campaign, with a focus on message imagery, use of graphic elements, and color selection. Qualitative analysis methods were used to examine the design elements of this social campaign with interview activities and their impact on the target audience. The results show that strong and relevant designs can strengthen social messages, motivate real action, and increase public awareness about the importance of becoming a bone marrow donor. The implications of these findings for the practice of social campaign design and efforts to increase participation in bone marrow donor programs are discussed in the context of this study. This analysis aims for other researchers to provide suggestions or conduct further research, and also improve the writer's ability to create a good campaign design, because campaign designs like this are very helpful in increasing public awareness of a problem.